2020
DOI: 10.1530/ec-19-0482
|View full text |Cite
|
Sign up to set email alerts
|

How treatments with endocrine and metabolic drugs influence pituitary cell function

Abstract: A variety of endocrine and metabolic signals regulate pituitary cell function acting through the hypothalamus-pituitary neuroendocrine axes or directly at the pituitary level. The underlying intracellular transduction mechanisms in pituitary cells are still debated. AMP-activated protein kinase (AMPK) functions as a cellular sensor of low energy stores in all mammalian cells and promotes adaptive changes in response to calorie restriction. It is also regarded as a target for therapy of proliferative disorders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…Dietary YSE significantly decreased the level of serum glucose in diabetic rats ( 33 ). The hypoglycemic function of YSE is related to its saponins ( 34 36 ). In this study, dietary supplementation of YSE decreased plasma MDA concentration and increased plasma SOD concentration, which may be related to the scavenging effect of YSE on superoxide free radicals or preventing the formation of superoxides or peroxides ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary YSE significantly decreased the level of serum glucose in diabetic rats ( 33 ). The hypoglycemic function of YSE is related to its saponins ( 34 36 ). In this study, dietary supplementation of YSE decreased plasma MDA concentration and increased plasma SOD concentration, which may be related to the scavenging effect of YSE on superoxide free radicals or preventing the formation of superoxides or peroxides ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metformin also contributes to the regulation of gonadotropin secretion and fertility through AMPK-mediated actions at the hypothalamic level and in pituitary gonadotroph cells, which have been recently reviewed [ 19 , 47 ].…”
Section: Molecular Mechanisms Underlying Metformin Actionsmentioning
confidence: 99%
“…Epidemiological studies and preclinical evidence have suggested the efficacy of metformin as a therapeutic agent for the treatment of two types of endocrine tumors, in detail differentiated thyroid cancer and pancreatic neuroendocrine tumors [ 13 , 16 , 17 ]. Furthermore, in vitro studies using cell lines and few studies in animal models have suggested to extend the efficacy of metformin to other endocrine tumors and contributed to characterize the differential effects of metformin in distinct cell types [ 18 , 19 , 20 ]. These laboratory-based data have not been confirmed by clinical evidence yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under nutrient-rich conditions, the inhibition of mTOR is diminished and the whole-body energy balance is positive, it is conducive to reproduction (Gonzalez et al, 2020). In addition to the above indirect effects on reproduction, AMPK in the hypothalamus and pituitary is able to directly regulate gonadal steroid hormones production and affect fertility in response to peripheral metabolic signals (Tulipano, 2020). However, the global physiological actions of AMPK in reproduction include not only the acute response of AMPK activation through directly phosphorylating downstream metabolic enzymes or regulating the hypothalamic pituitary gonadal (HPG) axis, but also AMPK-mediated transcriptional events via affecting the interaction between transcription regulators (TFs) and their DNA recognition sites.…”
Section: Introductionmentioning
confidence: 99%